Analysis of Candidate miRNAs' Expression in Pancreatic Cancer - Al‐Temaimi, Rabeah; Abdulkarim, Bicher; Al‐Ali, Ali; John, Bency; Mallik, Mrinmay Kumar; Kapila, Kusum (Cancer medicine (Malden, MA), 2024)
ABSTRACT Background Pancreatic cancer (PC) is one of the most aggressive types of cancer. Despite advances in molecular diagnostics, PC diagnosis relies on imaging technologies and morphological assessment of fine needle aspirates (FNAs). MicroRNA (miRNA) involvement in PC pathogenesis and potential diagnostics application have been suggested, albeit current supporting evidence is lacking. Here, we investigated the association of selected miRNAs with PC incidence and clinical characteristics. Methods Fold expression of miR‐216a‐3p, ‐217‐5p, ‐221‐3p, ‐222‐3p, and miR‐196a‐5p was assessed in 73 PC FNA cell‐block sections and 6 healthy pancreas tissues using Taqman advanced miRNA assays. Potential miRNA targets were ascertained using immunocytochemistry. Results miR‐196a‐5p was upregulated in PC compared to healthy pancreatic tissue (β = −0.05, 95% CI: −0.065 – (−0.035); p < 0.001). miR‐221‐3p and miR‐222‐3p fold expression were strongly correlated (r = 0.897, p < 0.001), whereas miR‐196a‐5p fold expression correlated with that of miR‐221‐3p (r = 0.688, p < 0.001) and miR‐222‐3p (r = 0.489, p < 0.001). Moreover, miR‐196a‐5p fold expression positively correlated with tumor stage (r = 0.32, p = 0.034). miR‐217‐5p fold expression inversely correlated with KRAS expression (r = ‐0.69, p = 0.0027). Conclusion Our study shows miR‐196a‐5p has reasonable specificity to PC and thus may have diagnostic and prognostic potential in PC as proposed in the literature. Moreover, KRAS and NFKBIA may be potential targets for miR‐217‐5p and miR‐196a‐5p, respectively. Thus, these miRNAs may be involved in tumor progression and may have valuable applications in novel therapeutics or treatment monitoring. miR‐196a‐5p upregulation in pancreatic cancer is associated with cancer progression. miR‐217‐5p is downregulated in pancreatic cancer allowing for KRAS overexpression.